2017
DOI: 10.1007/s10368-017-0398-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of bubble dynamics in the Chinese real estate market: a State space model

Abstract: This paper analyses the existence of a bubble in the Chinese real estate market and examines its driving factors with a state-space model. The model considers macroeconomic and real estate time series variables as inputs and employs a Kalman filter to obtain an estimated fundamental price using demand and supply for Chinese real estate. We then measure the deviation between actual and estimated fundamental real estate prices to test for the existence of a bubble. We find evidence for the existence of a bubble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Schulz and Werwatz (2004) also use the state-space present value model in a hybrid model of hedonic pricing, with the objective of using the Kalman filter to extract the common price component in the housing market in Berlin. Other papers which have used different dimensions of the state-space approach to housing markets include Riddel (1999), Gabrieli et al (2018), Hui and Yue (2006) and Teng et al (2013).…”
Section: Background Literaturementioning
confidence: 99%
“…Schulz and Werwatz (2004) also use the state-space present value model in a hybrid model of hedonic pricing, with the objective of using the Kalman filter to extract the common price component in the housing market in Berlin. Other papers which have used different dimensions of the state-space approach to housing markets include Riddel (1999), Gabrieli et al (2018), Hui and Yue (2006) and Teng et al (2013).…”
Section: Background Literaturementioning
confidence: 99%
“…Based on Chinese data sets, this study contributes to international research on real estate markets and debates about the role of policy tools in regulating this market. While various fundamental approaches have been used to value real estate, as argued by Gabrieli et al (2018), speculative activity can also push prices higher due to herding behaviour and irrational expectations of future price gains, resulting in substantial price deviations from fundamental determinants. As a result, the expectation-driven cycles introduced by Lambertini et al (2013) have been increasingly used to model the booms and bursts in the real estate market (Deng et al, 2018).…”
Section: Household Non-mortgage Loansmentioning
confidence: 99%
“…In China, on the other hand, the issuance of highinterest dollar bonds by housing companies has raised the cost of financing them. Gabrieli et al (2018) found that almost all of the official interest rate changes over the past decade have been driven by policy goals focused on the housing market. Shi This literature review showed that although researchers focus more on the problems and risks of foreign bond financing of housing enterprises, financing methods and currencies, financial supervision, the impact of corporate bond issuance, etc., and provide reference and ideas for future research, it is insufficient.…”
Section: Study Of the Factors And Effects Of The Issuance Of Bonds Bymentioning
confidence: 99%